PENGOMPOSAN DAN EFEK KOMPOS SERASAH DAUN ACASIA MANGIUM L TERHADAP PERTUMBUHAN DAN PRODUKSI KACANG TANAH - Djukri, Djukri (Universitas Negeri Yogyakarta, 2005)
The objective of the research is to investigate the effect of the Acasia mangium L leaves rubbish compost on the growth and production of peanut.The peanut used is gajah variety. The Acasia mangium L leaves rubbish compost was used for the treatment materials given since the seedling time. The compost was mixed with the soil used for planting media. This research applied the Completely Randomized Design (CRD). The independent variables consisted of six levels i.e 0,10, 20, 30, 40, and 50 grams compost per polibag, each five replications. The dependent variables are height, fresh weight, dry weight at the end of the vegetative growth, and the sum of the fruit is counted after harvest. The data were analyzed using the analysis of variants (anova),The result of the research indicates that after receiving treatment,the height, fresh weight, and dry weight of peanut, on 30, 40, and 50 grams proportion of the compost weight are significant (p<0.05). The sum of the ghost on 40 and 50 grams proportion of compost weight, shows a significant result (p<0.05). The combination of the height, fresh weight, and dry weight parameters on 30, 40, and 50 grams compost weight, shows value of growth better than with other treatments.Key words: composting, growth, and production